2014
DOI: 10.5032/jae.2014.04116
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Work-Life Balance Ability, Job Satisfaction, and Professional Commitment among Agriculture Teachers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 54 publications
10
64
2
3
Order By: Relevance
“…Tait (2008) found resilient teachers had a high level of career satisfaction through their first year teaching despite reporting high levels of stress. Sorensen and McKim (2014) found a relationship between job satisfaction and professional commitment for agriscience teachers. Some evidence also suggest demographic factors could influence resilience (Rutter, 1979;1985).…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 88%
“…Tait (2008) found resilient teachers had a high level of career satisfaction through their first year teaching despite reporting high levels of stress. Sorensen and McKim (2014) found a relationship between job satisfaction and professional commitment for agriscience teachers. Some evidence also suggest demographic factors could influence resilience (Rutter, 1979;1985).…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 88%
“…One-third of agriculture teachers indicated a perceived challenge to achieve work-life balance, which raises concern for the profession (Murray, Flowers, Croom, & Wilson, 2011). While some literature confirmed the battle for teachers of agriculture to achieve work-life balance (Hainline, Ulmer, Ritz, Burris, & Gibson, 2015;Sorensen & McKim, 2014), other researchers have determined that agriculture teachers perceive themselves as capable of achieving work-life balance (Clark, Kelsey, & Brown, 2014;Sorensen & McKim, 2014;Sorensen, McKim, and Velez, 2016). Furthermore, researchers found a predictive relationship between teachers' perceptions of increased workload that interferes with family life and the probability of leaving the profession of teaching (Sorensen, McKim, & Velez, 2016).…”
Section: Personal Factorsmentioning
confidence: 99%
“…Moreover, a high, positive correlation exists between job satisfaction and an agriculture teacher's perceived level of self-efficacy, particularly for novice teachers of agriculture (Blackburn & Robison, 2008;Swan, Wolf, & Cano, 2011). In addition to beginning teachers' initially high levels of self-efficacy and career commitment (Knobloch & Whittington, 2003), researchers determined career commitment for experienced educators is a strong predictor for teacher retention (Crutchfield, Ritz, & Burris, 2013;Sorensen & McKim, 2014). Allen (2005) revealed the likelihood of a teacher leaving the profession significantly declines after year five.…”
Section: Teacher Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some studies discussing it find that Advice network across divisions and Perceived organizational culture are correlated with professional commitment to nurses [24], achievement motivation influences affective and normative commitment to profession [5], competence has positive impact to affective commitment, commitment to continuity, and normative commitment to the profession [4]. Another study says that the value employees have in work has a positive effect on professional commitment [6] Previous studies have shown that job satisfaction has a positive correlation with professional commitment [3] [17], which means that employees who are satisfied with their work will be followed by increased professional commitment. The concept of job satisfaction has similarities with the definition of quality of work life, that is the evaluation of all things that have been obtained by employees in their work.…”
Section: Introductionmentioning
confidence: 99%